Post-disaster consumption: analysis from the 2011 Christchurch earthquake. Issue 1 (1st January 2017) - Forbes, Sharon L.
Abstract: This unique study provides information to logistics managers, retailers and governments about how consumer behaviour is modified following a large-scale disaster in a developed nation. Scanner data of purchases made in Christchurch supermarkets before and after the 2011 earthquake was used to identify immediate and short-term changes in consumer behaviour. In the immediate aftermath, consumers purchase increased levels of utilitarian products necessary for survival (e.g. water and non-perishable foods), but there is no evidence of increased consumption of hedonic or potentially harmful products. However, higher consumption of hedonic and harmful products does occur in the weeks after the disaster.